2016
DOI: 10.3389/fnhum.2016.00068
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Combined with Aerobic Exercise to Optimize Analgesic Responses in Fibromyalgia: A Randomized Placebo-Controlled Clinical Trial

Abstract: Fibromyalgia is a chronic pain syndrome that is associated with maladaptive plasticity in neural central circuits. One of the neural circuits that are involved in pain in fibromyalgia is the primary motor cortex. We tested a combination intervention that aimed to modulate the motor system: transcranial direct current stimulation (tDCS) of the primary motor cortex (M1) and aerobic exercise (AE). In this phase II, sham-controlled randomized clinical trial, 45 subjects were assigned to 1 of 3 groups: tDCS + AE, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(189 citation statements)
references
References 41 publications
5
152
0
7
Order By: Relevance
“…Therefore, a single stimulation session might not be enough to generate important clinical changes. Finally, it is more and more evident that the effects of tDCS seem to be greater when coupled with a specific task [3840]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a single stimulation session might not be enough to generate important clinical changes. Finally, it is more and more evident that the effects of tDCS seem to be greater when coupled with a specific task [3840]. …”
Section: Discussionmentioning
confidence: 99%
“…In nine studies using a structured questionnaire on the occurrence of AEs in migraine (Antal et al, 2011a; Dasilva et al, 2012; Poreisz et al, 2007; Wickmann et al, 2015), fibromyalgia (Fagerlund et al, 2015; Mendonca et al, 2016), temporomandibu-lar disorders (Donnell et al, 2015), irritable bowel syndrome (Volz et al, 2016), or a mixture of various neuropathic and non-neuropathic pain syndromes (Antal et al, 2010) the frequency of reported AEs was 20–50% higher than in studies with spontaneous reporting. Here also the most frequent AEs were tingling at the stimulation site (51% of either active or sham), and sleepiness or fatigue (39% after active and 45% after sham).…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…For example, transcranial magnetic stimulation (rTMS) involves using a magnetic field generator to stimulate small regions of the affected brain region. Thus far, rTMS has been shown to be an effective treatment for burning mouth syndrome [191], complex regional pain syndrome [192], fibromyalgia [193,194], neuropathic pain [195,196,197], depressive disorders [198] and to a lesser degree PTSD and other anxiety disorders [199,200]. It has been proposed to prevent or revert the ongoing maladaptive plasticity within the pain matrix [201], and modify opioidergic, glutamatergic, gamma-aminobutyric acidergic, and serotoninergic neurotransmissions [202].…”
Section: Treatments For Comorbid Chronic Pain In Youthmentioning
confidence: 99%